Entrepreneurial bricolage and its effects on new venture growth and adaptiveness in an emerging economy - Yu, Xiaoyu; Li, Yajie; Su, Zhongfeng; Tao, Yida; Nguyen, Bang; Xia, Fan (Asia Pacific journal of management, 2020)
Driven by solid economic developments, emerging economies are experiencing significant institutional change, particularly in regulatory structures and market systems. Coupled with fierce market competition and reforms, serious challenges for the sustainable development of new ventures are created due to smallness and newness liabilities. This study examines how new ventures grow and adapt to the rapid environmental shifts in emerging economies by exploring the effects of entrepreneurial bricolage. This study found that entrepreneurial bricolage has a positive impact on both new venture growth and adaptiveness. Further, institutional voids have contrasting effects on these two relationships. The effectiveness of entrepreneurial bricolage on new venture growth is stronger in a context with serious institutional voids, while the effectiveness of entrepreneurial bricolage on new venture adaptiveness is weaker in a context with serious institutional voids. These findings not only enrich our knowledge on the implications of entrepreneurial bricolage, but also advance our understanding of the emerging economy context.